Antiulcerosos inhibidores de la bomba de protones en pacientes atendidos en un establecimiento farmacéutico de Trujillo, enero – diciembre 2018 - Ortiz Lujan, Mario Janfranco (2019)
The purpose of this research is to determine and identify the frequency of the use of antiulcer proton pump inhibitors (PPI) and to identify factors associated with these, in patients treated in a private pharmaceutical establishment in Trujillo, from January to December 2018. We interviewed 292 patients who consume antiulcer PPI. Using a data collection card, the sex, age, marital status, and degree of instruction of the patients were recorded. In addition, the prescribed pharmacological group and the indications of the PPI medications were also considered, in order to establish the relationship of the factors associated with the treatment. The anti-ulcer PPI with the highest frequency of use was esomeprazole with 30.83% compared to its competitors in the same pharmacological group. Among the associated factors considered in patients who use anti-ulcer PPIs, 66.44% of patients are male, 28.08% of patients are under 40 years old, 41.78% are married and 51. 71% have higher education. On the other hand, 44.95% have a good knowledge of the pharmacological indications, dose, dosage interval and duration of treatment; and 44.35% comply with the pharmacological indications, dosage, dosage interval and duration of treatment